THE TRIPS WAIVER AND GLOBAL HEALTH EQUITY - Lam, Nguyen Tung (International Journal of Research -GRANTHAALAYAH, 2025)
This research paper critically examines the proposal for a patent waiver under the TRIPS Agreement in response to the COVID-19 pandemic, with a primary goal of evaluating its effectiveness in promoting global health equity. The study adopts a qualitative research design, employing a doctrinal legal methodology to analyze international legal frameworks, WTO documents, and scholarly literature. It assesses both the arguments supporting and opposing the PW, focusing on its potential to enhance vaccine accessibility and affordability, particularly in least developed nations. The analysis reveals that while the waiver could facilitate wider vaccine production by eliminating intellectual property barriers, it faces significant opposition due to concerns about undermining incentives for innovation and weakening the global intellectual property regime. The paper also highlights practical challenges in implementing such a waiver, including legal complexities and the absence of a robust enforcement mechanism. Furthermore, it explores existing TRIPS flexibilities, such as compulsory licensing, as alternative strategies that might balance intellectual property protection with public health needs. The findings suggest that although the patent waiver has symbolic and practical merit in addressing immediate health crises, its long-term viability as a model for future pandemics is limited. The study concludes that rather than relying solely on patent waivers, a more sustainable approach would involve strengthening domestic intellectual property legislation, promoting voluntary licensing, and fostering international cooperation to ensure equitable access to essential medicines and vaccines during global health emergencies.